Profiling of B-Cell Factors and Their Decoy Receptors in Rheumatoid Arthritis: Association With Clinical Features and Treatment Outcomes - Rodríguez-Carrio, Javier; Alperi-López, Mercedes; López, Patricia; Ballina-García, Francisco J.; Suárez, Ana (Frontiers in Immunology, 2018)
Introduction: B-cell activation is pivotal in rheumatoid arthritis (RA) pathogenesis and represents a relevant therapeutic target. The main aim of this study was to characterize the profiles of B-cell factors and their decoy receptors in RA and evaluate their clinical relevance. Methods: sBLyS, sAPRIL, sBCMA, sTACI, sBLyS-R and several cytokines’ serum levels were measured by immunoassays in 104 RA patients and 33 healthy controls (HC). An additional group of 42 systemic lupus erythematosus (SLE) patients were enrolled as disease controls. Whole blood IFI44, IFI44L, IFI6 and MX1 gene expression was measured and averaged into an IFN-score. BLyS membrane expression (mBLyS) was assessed on blood cell subsets by flow cytometry. Results: increased sAPRIL and sBCMA levels were found in RA, whereas BLyS was elevated in very early RA (VERA). No differences were observed for sTACI and sBLyS-R. An increased sBLyS/sBLyS-R ratio was associated with poor clinical outcome at 6 and 12 months in VERA, whereas a positive association with disease activity was observed in established disease. Increased mBLyS expression was found on monocytes, mDCs, neutrophils and B-cells in RA, to a similar extent that in SLE patients. Cluster analysis identified a specific B-cell factors profile overrepresented in RA and associated with autoantibodies, elevated proinflammatory cytokines (IFNa, MIP1a, TNFa, IL-37 and GM-CSF) and increased type-I IFN signature. Increasing sBCMA and sBLyS serum levels upon treatment and mBLyS expression at baseline on monocytes and mDCs, but not B-cells, were associated with poor clinical outcome upon TNFa-blockade. Conclusions: profound and complex alterations of soluble and membrane-bound B-cell factors are observed in RA associated with clinical outcomes, thus supporting its applicability to guide patient stratification along disease course.